AMELIORATIVE ACTION OF Tribulus terrestris ON ATRAZINE EXPOSED FRESH WATER FISH Oreochromis mossambicus (W. K. H. Peters, 1852) - NIMAVATHI, V.; JAYANTHI, J.; RAGUNATHAN, M. G. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
The present investigation is designed to compare to study of responses when conducted in freshwater fish Oreochromis mossambicus exposed at sublethal concentration of atrazine (16.5 mg/L) in 120 hours. The results revealed that treatment of atrazine enhanced the level of the hepatic enzyme activity of alanine transaminase (ALT), aspartate transaminase (AST), alkaline phosphatase (ALP) and lactate dehydrogenase (LDH). Subsequently the treatment of Tribulus terrestrisis active constituents at a dose of 1.2 g/L drastically restored to the normal levels of all hepatic enzymes (AST, ALT, ALP and LDH). Therefore our experimental studies suggest that the administration of Tribulus terrestris is proved to be the best ameliorative agent for atrazine herbicide which induced the damage in hepatic.